Pengelolaan Program Life Skill Menjahit Tingkat Dasar dalam Upaya Menumbuhkan Jiwa Kewirausahaan Peserta Didik Kejar Paket C di UPT Sanggar Kegiatan Belajar (SKB) Gresik - Rohmatul Ummah; Widodo Widodo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
The Life Skill programme is determined by UPT Sanggar Kegiatan Belajar (SKB) Gresik according to the learning needs of students, one of which is the basic level sewing Life Skill programme. This study aims to describe the management of the basic level sewing life skills programme in fostering the entrepreneurial spirit, and describe the supporting factors and inhibiting factors of the basic level sewing life skills programme. This research method uses a qualitative approach with descriptive methods at UPT Sanggar Kegiatan Belajar (SKB) Gresik. Data collection techniques in this research use in-depth interview techniques, participatory observation, and documentation. Data analysis techniques include data collection, data reduction, data display, and conclusion verification. The data validity criteria include internal validity (Credibility), external validity (Transferability), and dependability (Vaiability), objectivity (Confirmability). The results of this study are the management of the basic level sewing life skills program based on planning, organising, implementing, and supervising. However, there are several aspects that have not been implemented properly which affect the development of the basic level sewing life skills programme. Efforts to foster an entrepreneurial spirit in students can be seen through the learning process of the basic level sewing Life Skill programme which includes aspects of hard work, discipline, risk-taking, and creative and innovative